Analisis Relevansi Materi Superkelas Pisces dalam Aspek Penerapan Ilmu Taksonomi Hewan di Sekolah: (Analysis of the Relevance of Pisces Superclass Material in the Aspect of Application Animal Taxonomy in Schools) - Rhavy Ferdyan; Abdul Razak; Ramadhan Sumarmin; Zulyusri Zulyusri (BIODIK, 2020)
The science of taxonomy animal is a science that is constantly experiencing growth. One of the objects of study of the taxonomy of animals is a superclass Pisces that its application is also done at the school through the teaching of biology. To expand the repertoire of science knowledge regarding Pisces, not be separated fromÂ research that are continuously being developed by experts to produce discoveries about the Pisces superclass which also have an impact on the discovery of new concepts. Will but the content material superclass Pisces on learning and several book packages that use has not been demonstrated progress hot, even still finding misconception. This is certainly not appropriate if it is still implemented. Through the articles of this author will give a review of the science regarding the reason for the importance of increasing the relevance of the content material to expose the data and facts state of content material superclass Pisces during this. Articles of this come through research by using approach qualitative type of study library (library research). Abstrak. Ilmu taksonomi hewan merupakan ilmu yang senantiasa mengalami perkembangan. Salah satu objek kajian taksonomi hewan adalah superkelas pisces yang penerapannya juga dilakukan di sekolah melalui pembelajaran biologi. Untuk memperluas khasanah ilmu pengetahuan mengenai pisces, tidak akan lepas dari penelitian-penelitian yang terus dikembangkan oleh para ahli untuk menghasilkan penemuan-penemuan baru tentang superkelas pisces yang juga berdampak kepada penemuan konsep-konsep baru. Akan tetapi konten materi superkelas pisces pada pembelajaran dan beberapa buku paket yang digunakan belum menunjukkan perkembangan terkini, bahkan masih ditemukannya miskonsepsi. Hal ini tentu tidak tepat jika masih diterapkan. Melalui artikel ini penulis akan memberikan kajian ilmiah mengenai alasan pentingnya meningkatkan relevansi konten materi dengan memaparkan data dan fakta keadaan konten materi superkelas pisces selama ini. Artikel ini hadir melalui penelitian dengan menggunakan pendekatan kualitatif tipe studi pustaka (library research).